METABOLIC IMPLICATIONS OF PERITONEAL DIALYSIS IN PATIENTS WITH ACUTE KIDNEY INJURY - Goes, Cassiana Regina [UNESP]; Berbel, Marina Nogueira [UNESP]; Balbi, André Luis [UNESP]; Ponce, Daniela [UNESP] (Multimed Inc, 2013)
Background: Peritoneal dialysis (PD) is a treatment for selected acute kidney injury patients (AKI), but little is known about its metabolic implications. The aim of the present study was to evaluate the metabolic implications of glucose absorption, sodium removal, protein loss into the dialysate, and catabolism in AKI patients undergoing high-volume PD and to identify risk factors associated with those metabolic effects.Methods: A prospective cohort study over 18 consecutive months evaluated 208 sessions of high-volume PD performed in 31 AKI patients. One session of high-volume PD lasted 24 hours. Repeated-measures analysis was performed, and correlations were calculated using the Spearman test for continuous variables and generalized linear models for categorical variables.Results: Glucose absorption remained at approximately 35.3% +/- 10.5% per session. Protein loss measured 4.2 +/- 6.1 g daily, with higher values initially, which declined significantly after 2 sessions. Nitrogen balance (NB) was initially negative, but stabilized at approximately zero after 3 sessions. Glucose uptake was positively correlated with the Acute Tubular Necrosis Individual Severity Score [ATNISS (r = 0.21, p = 0.0036)], C-reactive protein (r = 0.26, p = 0.0167), protein loss (r = 0.36, p < 0.0001), and sodium removal (r = 0.24, p = 0.002). Protein loss was positively correlated with sodium removal (r = 0.22, p = 0.0085) and gastrointestinal disease (p = 0.0004). Sodium removal was positively correlated with serum sodium (r = 0.21, p = 0.0064), ATNISS (r = 0.15, p = 0.0411), urea nitrogen appearance [UNA (r = 0.24, p = 0.0019)], and fluid overload as an indication for dialysis (p < 0.0001). Urea nitrogen appearance was positively correlated with the indication for dialysis (electrolyte disturbances: p = 0.0287) and negatively correlated with nephrotoxic AKI (p < 0.0001). Nitrogen balance was negatively correlated with UNA (r = -0.389, p < 0.0001) and ischemic AKI (p = 0.0047).Conclusions: High-volume PD did not increase hypercatabolism in AKI patients, and protein loss and glucose uptake remained constant during treatment. Those parameters were influenced by the clinical condition of the patients, including the cause of AKI, inflammation, and comorbidities-factors that should be known before the prescription of dialysis and nutrition, thus avoiding metabolic complications such as hyperglycemia, hypernatremia, and worsening catabolism.
Keywords: Acute kidney injury; metabolic implications